STUDIES ON CROSS-LINKED CHITOSAN HYDROGEL FOR MATRIX TABLETS OF MONTELUKAST SODIUM - Hebbar, Srinivas; Dubey, Akhilesh; S., Ravi G.; Mascarenhas, Shanon Ben (International Journal of Applied Pharmaceutics, 2017)
Objective: The aim of the present study was to prepare hydrogel matrix tablets for controlled release of an anti-asthma drug (Montelukast sodium) by modifying the applications of chitosan by crosslinking it with the different cross linking agent. Methods: The hydrogels were prepared by crosslinking chitosan using three different crosslinking agents namely, anhydrous dextrose (DXT), sodium tripolyphosphate (TPP) and glutaraldehyde (GL). Formulations were prepared by direct compression method and pre and post compression parameters were evaluated. Results: FTIR (Fourier transform infrared spectroscopy) studies of tablet formulation indicated that there is no drug-excipient interaction in the prepared formulations. The matrix tablets were capable of releasing the drug for 11 h depending upon the formulation variables. The tablets prepared by plain chitosan discharged the drug quickly, while those prepared by using GL crosslinked-hydrogel released the drug more slowly in a controlled manner. In general, the order of drug release from the crosslinked hydrogel matrix tablets on the basis of crosslinking agents, was found to be DXT>TPP>GL. The type of cross-linking agents affected the drug release rate and in the case of the tablets prepared with CHTPP (95 % to 83 %) it was slower than for the tablets prepared with CHDX (96 % to 88 %) at the end of 11th h. CHGL tablets showed more prolonged drug release profiles (86 % to 74 %) as compared to CHDX and CHTPP at the end of 11th h. In vitro release data was fitted into various release kinetic models to study the release mechanism and showed zero order kinetics and nâ€ value were found to be less than 0.5 indicated the release mechanism followed fickian diffusion due to swelling of gel matrix and high solubility of montelukast sodium. Conclusion: From the experimental results it can be concluded that hydrogels of chitosan were successfully prepared by using DXT, TPP and GL with different concentration.